Does the repeat dose of gonadotropin-releasing hormone agonist trigger in polycystic ovarian syndrome improve in vitro fertilization cycles outcome? A clinical trial study - Abbas Aflatoonian; Fatemeh Haghighi; Masrooreh Hoseini; Saeid Haghdani (International Journal of Reproductive BioMedicine, 2020)
Background: A repeat dose of Gonadotropin-releasing Hormone (GnRH) agonist could provide long duration of luteinizing hormone (LH) surge and amplitude appropriately. Objective: Improvement in oocyte maturity could be obtained by a repeat dose of GnRH agonist. Materials and Methods: In this randomized double-blinded study, 120 women with polycystic ovarian syndrome and serum estradiol level (E2)